The Effect of the Gallery Walk Cooperative Learning Model on Learning Outcomes in Economics Lessons - Nadiminsyah; Wahjoedi; Utomo, Sugeng Hadi (Journal of Educational Analytics, 2024)
Cooperative learning is different from other learning. The difference can be seen from the learning process which emphasizes the process of cooperation in groups. The goal to be achieved is not only academic ability in terms of mastery of learning materials but also the element of cooperation to master the material. The existence of this cooperation is what characterizes Cooperative learning. This study aims to analyze student learning outcomes in economic subjects. The sample of this research is class X students of SMA Negeri 1 Madapangga. The instruments to be used in this research are tests, observation sheets, documentation, and questionnaires. Data analysis techniques used in this research are descriptive statistical analysis techniques and inferential statistical analysis techniques that aim to examine the research variables. The results concluded that the application of the gallery walk-type cooperative learning model to student learning outcomes in economic subjects had a significant and positive influence, with the contribution of variable x to variable y amounting to 61.2%.